FUNGSI RAWA PESISIR SEBAGAI HABITAT SIDAT TROPIS Anguilla spp. DI ESTUARI SUNGAI CIMANDIRI, SUKABUMI JAWA BARAT - Triyanto; Ridwan Affandi; Mohammad Mukhlis Kamal; Gadis Sri Haryani (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
The coastal swamp is a tidal swamp part of the estuary ecosystem. Coastal swamp on the Cimandiri River, Sukabumi West Java is one of the estuarine ecosystems that have an important ecological role for the lives of sedentary aquatic biota and migratory fish such as eels. The objectives of this study were to determine the population biology of eels and influential environmental factors in the coastal swamp of the Cimandiri River. The study conducted partially in September-October 2016, March and December 2017 and January-November 2018. Eel fishing and water quality measurements were carried out in 4 selected locations based on different habitat conditions. Eel fishing is done at night with fishhooks and traps. There were two species of tropical eel, Anguilla bicolor bicolor (107 individuals) and Anguilla marmorata (4 individuals). The total length of A. bicolor bicolor is 15.7-57.0 cm and weight 5.8-347.2 g. The total length of A. marmorata is 17.0-29.5 cm and weight 6.9-33.7 g. The growth pattern of A. bicolor bicolor in the coastal swamp was negative allometric, with the condition factor values ​​0.99-1.03. Based on Principal Component Analysis (PCA), the preferences for the presence of eel in coastal swamp are characterized by parameters of depth, transparency, salinity, and water current. From this study, it is known that the coastal swamp has functioned as a habitat for yellow eels in the estuarine phase.